Management and Prognosis of Acute Post-Cataract Surgery Endophthalmitis: A 10-Year Retrospective Analysis in Eastern China - Xiuwen Zhang; Zhi Chen; Xiaoxia Li; Zimei Zhou; Maureen Boost; Taomin Huang; Xingtao Zhou (MDPI AG, 2023)
Acute post-cataract surgery endophthalmitis (APSE) is a serious vision-threatening complication of cataract surgery. Analysis of the management and prognosis in cases of APSE may provide better guidance for future treatment. Fifty-six patients (56 eyes) diagnosed with APSE between 2013 and 2022 were retrospectively reviewed. The incidence of APSE rate was 0.020% (95% CI: 0.011-0.029%). Intraocular cultures were positive in 18 (32.1%) cases, with 21 organisms isolated. Coagulase-negative staphylococci was the predominant isolate (12/21; 57.1%). The time from surgery to the onset of endophthalmitis was 7 days (interquartile range: 3-16) in patients with good best-corrected visual acuity (BCVA) (≥20/70) and 3 days (interquartile range: 1-8) in those with poor BCVA (<20/70). Multivariate linear regression analysis revealed that initial BCVA (logMAR) (p < 0.001), time from onset to initial intravitreal antibiotics (IVAs) (p < 0.001), and positive culture of highly virulent pathogens (p = 0.018) displayed significantly positive associations with the final BCVA (logMAR). Adjunctive use of intravitreal corticosteroids and systemic antibiotics were unrelated to a favorable final BCVA. In conclusion, the severity of the visual condition at baseline, as well as delayed treatment, are risk factors for poor visual outcomes in APSE.